(untitled) (Revista de Artes Marciales Asiáticas, 2023)
This short report describes the process of creating the Combat Sports Special Interest Group (CSSIG), its first meeting at the 28th Annual Congress of the European College of Sport Science (ECSS, Paris 4-7 July, 2023), and to make a call for action for the next events. The first contact between the group that proposed the creation of the CSSIG was made after a session of the Annual Congress of the ECSS held in 2022, but the idea and format of the proposal was initiated in January 2023. After its approval the CSSIG set the topics for the first meeting. During the 2023 edition the ECSS event had eight special interest groups, including the CSSIG. The first meeting of the CSSIG included the presentation of its goals, and two short presentations: one related to combat sports athletes’ health, and the other on testing and training monitoring of judo athletes. The aim of the CSSIG is to establish a sustainable network fostering evidence-based research and practice of combat sports, in order to: (a) promote health and safety of combat sports participants, (b) enhance their performance, and (c) improve training and competition practices. Thus, this report is also a call for action for the next events.